Instrument to evaluate to which extent the operational support information system (OSIS) adds value to the South African Air Force (SAAF) - Hattingh, Maria Jacoba (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MMil (Computer Information Systems))--University of Stellenbosch, 2005.